Reacting to the entry of green manufacturers: A perspective from ordinary manufacturers - Zhang, Linghong; Yu, Wenchao (Frontiers in Environmental Science, 2023)
More and more green manufacturers enter the market, which poses a challenge to ordinary manufacturers: whether the ordinary manufacturers need to produce environmental product. Motivated by competition between the green manufacturer and the ordinary manufacturer, this study examines how an ordinary manufacturer who produces a traditional product (product 1) adapts its product portfolio to compete with the new entrant green manufacturer. The sale period is divided into two periods. In period 1, the green manufacturer enters the market and provides one green product, product 2, Subsequently, the ordinary manufacturer decides whether developing a green product (product 3) in period 2. The products are differentiated in two characteristics: the traditional quality and the environmental quality. We derive the demand function by comparing the consumer utility obtained from the three products. Then we investigate the ordinary manufacturer’s and green manufacturer’s optimal decisions using the game theory. Further, we study how the government subsidy towards green product affects the two manufacturers’ decisions. Finally, we extend our model to discuss the market position of the two green products when the green technology level is fix for two manufacturers. Our study suggests that (1) the ordinary manufacturer may not introduce the green product, when the difference of the environmental quality between two green products is much larger; (2) the government subsidy is effective in stimulating the ordinary manufacturer to introduce green product, especially when the traditional manufacturer could provide high environmental quality product; (3) manufacturer’s green technology level, the green technology maturity and consumers’ willingness to pay for the traditional quality together affect product position.